Renal Cortical Transit time as a predictor for pyeloplasty in paediatric patients with unilateral hydronephrosis at the Red Cross War Memorial Children's Hospital - More, Stuart Setjhaba (Division of Radiology, 2019)
Background: Majority of patients with unilateral hydronephrosis (HN) detected on ultrasound (US) do not require pyeloplasty. Indications for pyeloplasty are in patients with symptomatic obstruction (recurrent flank pain), complications such as urinary tract infection, a drop in differential renal function (DRF) of more than 10% and a progressive increase in the anterior posterior diameter (APD) in subsequent studies. Schlotmann et al, Piepsz et al and Harper et al have demonstrated the measurement of the cortical transit time (CTT) to predict the need for patient who may require pyeloplasty. Objectives: To assess if the CTT would have predicted a drop in DRF in patients with unilateral HN on the affected side. In addition to assess whether the CTT would differ on the first renogram between those patients who had a pyeloplasty and those who did not have a pyeloplasty at the Red Cross War Memorial Children’s Hospital (RCWMCH). Methods: Sixty eight (68) patients with at least two renograms with unilateral HN with a normal contralateral kidney were observed retrospectively between December 2000 and May 2015. The CTT was recorded for the upper, middle and lower third of each kidney and the mean used as the CTT of the kidney. Each renogram was processed three times to measure the DRF using the Rutland Patlak and Integral methods. The mean of the three DRF measurements was used for analysis. Results: The mean CTT of the left and right hydronephrotic kidneys were 6.0minutes and 6.7minutes respectively. A significant relationship was demonstrated in the CTT and DRF as well as CTT and APD in the first renogram of those patients who did not have a pyeloplasty (p < 0.05). There was no difference between the DRF of the first and second renograms in those patients who did not have a pyeloplasty. In the 20 patients who had a pyeloplasty, there was a drop of more than 10% in the DRF of 3 patients. No difference was seen in the DRF or in the CTT between the first and second renogram. The CTT was shorter in the second renogram in 9 of the 20 patients who had a pyeloplasty. No significant difference was found in the CTT or DRF when comparing the group who had surgery against the group who did not have surgery. Conclusion: The current study was unable to demonstrate in our series of patients that CTT can predict those patients who would require pyeloplasty. This may be owing to the retrospective nature of the study and the reliance on the clinical notes for the US data and surgical notes. In future, a prospective study evaluating the relationship between CTT and a drop in the DRF should be undertaken in this unit.